Significance of the intraoperative methylene blue test for postoperative evaluation of the vesicourethral anastomosis - Nyarangi-Dix, Joanne; Pahernik, Sascha; Lorenzo Bermejo, Justo; Prado, Lucas G.; Hohenfellner, Markus (Advances in urology, 2012)
We prospectively investigated whether routine evaluation of the vesicourethral anastomosis (VUA) after radical prostatectomy can be waived. Primary integrity of the VUA was analysed by an intraoperative methylene-blue test (IMBT) and postoperatively by conventional cystography. Data on the IMBT, contrast extravasation and prostate volume as well as pad usage were collected prospectively. Significantly more patients with a primary watertight anastomosis demonstrated by the MBT had no leakage in the postoperative cystography (). In a multivariate logistic regression with adjustment for prostate size and surgeon, the positive correlation between IMBT and postoperative cystography remained statistically significant (). The IMBT is easy to perform, inexpensive, and timesaving. With it postoperative evaluation of VUA for integrity can be waived in a significant number of patients. Following our algorithm, the Foley can be removed without further testing of the VUA, whenever the IMBT detected no leakage.
Gesehen am 05.04.2018